An Insight into MptpB Inhibitors as a Key Strategy to Treat MDR and XDRTuberculosis - Jain, Madhur; Gollapudi, Sirisha; Khatik, Gopal L. (Current Pharmaceutical Design, 2023)
Tuberculosis (TB) is a chronic, air-borne infectious disease caused by Mycobacterium tuberculosis (Mtb), which prominently affects the lungs and usually manifests in other organs. TB is preventable and curable but what makes it challenging is the emergence of resistance to the available treatment options. MDR-continued TB's expansion is one of the world's most pressing and difficult problems. Mtb revives via the reciprocity between Mycobacterium and host signalling pathways. Mtb secretes a virulence component called Mycobacterium tuberculosis protein tyrosine phosphatase (MptpB), which helps to survive against host macrophages. It indicates that targeting secreted virulence factors offers more benefits to circumvent the emergence of resistance. Many effective inhibitors of MptpA and MptpB have been discovered, providing a solid foundation for future research and development. Aside from possessing a structurally unique binding site in the Mtb enzyme, MptpB's minimal resemblance to other human phosphatases provides a broad platform for improving selectivity over host PTPs. We believe that addressing several parts of infection processes in the host and bacteria with combination therapy is the greatest way to reduce treatment burden and medication resistance. We have discussed the recent potent, selective, and efficacious MptpB inhibitors, such as natural and marine-based, isoxazole- linked carboxylic acid-based, oxamic acid-based, and lactone-based inhibitors, as potential strategies for treating TB.
Keywords: MDR-TB